Contamination of honey products by Clostridium botulinum spores and fungi along with their effects on human health - Yahya Ebrahimi; Andrés Alexis Ramírez-Coronel; Aiman Mohammed Baqir Al-Dhalimy; Raed H. C. Alfilm; Mohammed Al-Hassan; Rasha Fadhel Obaid6; Ameer A. Alameri; Fatemeh Rastiani; Yousef Khaledian; Samira Shokri (Caspian Journal of Environmental Sciences, 2022)
Bee products, such as honey, are widely consumed as food and medicine. Because of its sticky nature, honey does absorb bacterial spores from dust or bee activity, and their contamination may carry serious health hazards. Databases searched to obtain articles included “Google Scholar”, “SID”, “Scopus”, “PubMed”, “Science Direct”, and “ISI”. Keywords used in this study included Clostridium botulinum, Honey, bees, fungi in their titles. This study focused on published articles from 2016 to 2022. Result showed that this product may contain a great variety of bacteria and particularly, fungi that eventually entered the food chain at an early stage (e.g., via pollen). The ranges of samples with C. botulinum, yeast and mould infections were 0.5% - 68%, 15.78% - 100% and 17.22 - 100%, respectively. Overall, the amount of honey contaminated with Cl. botulinum spores, yeast, and molds in some of the samples that were evaluated was nil, however certain samples from the Lithuanian Kazakh, Turkey, and Brazil regions exhibited varying levels of contamination.